Research Advances in Myocardial Infarction Repair and Cardiac Regenerative Medicine via the Notch Signaling Pathway - Songyan Cai; Qingyuan Dai (Reviews in Cardiovascular Medicine)
Acute myocardial infarction is myocardial necrosis caused by acute and persistent ischemia and hypoxia in the coronary artery and severely affects public health. Recently, stem cell research has presented transformational developments in treating myocardial infarction. The Notch signaling pathway plays a crucial role in the post-myocardial infarction repair process and cardiac regenerative medicine. Additionally, the Notch signaling pathway can be involved in regulating the inflammatory response, myocardial fibrosis, oxidative stress, cardiomyocyte apoptosis, and cardiomyocyte regeneration after myocardial infarction. Moreover, the Notch signaling pathway is applied in cardiac tissue engineering. This review mainly elaborates on the research on the Notch signaling pathway in repairing myocardial infarction and cardiac regenerative medicine, aiming to provide a reference for treating acute myocardial infarction.